The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1016/s0896-6273(02)00614-1
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Trafficking Patterns Due to Multiple Traffic Motifs in G Protein-Activated Inwardly Rectifying Potassium Channels from Brain and Heart

Abstract: G protein-activated inwardly rectifying potassium channels (Kir3, GIRK) provide an important mechanism for neurotransmitter regulation of membrane excitability. GIRK channels are tetramers containing various combinations of Kir3 subunits (Kir3.1--Kir3.4). We find that different combinations of Kir3 subunits exhibit a surprisingly complex spectrum of trafficking phenotypes. Kir3.2 and Kir3.4, but not Kir3.1, contain ER export signals that are important for plasma membrane expression of Kir3.1/Kir3.2 and Kir3.1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
208
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(226 citation statements)
references
References 47 publications
18
208
0
Order By: Relevance
“…By taking the proposed arrangement of the P2X 2/3 subunits as valid, this suggests that one P2X 2 subunit is sufficient to stabilize the whole channel complex at the cell surface. Similar rescue of the surface expression of trafficking deficient ion channels by Wt subunits has been reported for the homo-oligomeric Kir2.1 and hetero-oligomeric Kir3 inward rectifier potassium channel (33). Kir channels have a tetrameric subunit organization; however, the number of Wt Kir subunits that are sufficient to drive the surface expression of the channel complex has not been documented.…”
Section: Discussionmentioning
confidence: 61%
“…By taking the proposed arrangement of the P2X 2/3 subunits as valid, this suggests that one P2X 2 subunit is sufficient to stabilize the whole channel complex at the cell surface. Similar rescue of the surface expression of trafficking deficient ion channels by Wt subunits has been reported for the homo-oligomeric Kir2.1 and hetero-oligomeric Kir3 inward rectifier potassium channel (33). Kir channels have a tetrameric subunit organization; however, the number of Wt Kir subunits that are sufficient to drive the surface expression of the channel complex has not been documented.…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies have shown that an epitope insertion in these positions has no detectable effects on the function of Kir channels or GPCRs (19)(20)(21)(22). Compared with an empty vector control, overexpression of AGS3 caused an increase in the total protein levels of most receptors and channels assayed (Fig.…”
mentioning
confidence: 79%
“…Thus, we determined whether this co-assembly with L18A/L25A would inhibit cell surface expression of wild type channel. For these studies we transiently co-transfected wild type and mutated channel into HEK cells and evaluated cell surface expression of the HA-tagged channel using both IF as well as a chemiluminescence assay (29). As shown in Fig.…”
Section: Fig 2 Mutations In the Nh 2 -Terminal Dileucine And Leucinmentioning
confidence: 99%
“…6A, right panel). These effects were more quantitatively addressed using the chemiluminescence-based assay devised by Jan and colleagues (29). As shown in Fig.…”
Section: Fig 2 Mutations In the Nh 2 -Terminal Dileucine And Leucinmentioning
confidence: 99%